A Case of a Derivative Chromosome: der(Y)t(Y;18)Pat with Congenital Abnormalities. (20th May 2021) - Huang, Shufang; Xia, Yu; Ding, Hong; Wang, Yonghua; Wu, Yueheng; Chen, Shaoxian; Zhuang, Jian; Li, Ping
Abstract: Background: Chromosome reciprocal translocations are frequently occurring structural rearrangements observed in humans. Although individuals with balanced reciprocal translocations tend to be clinically normal, they have an increased risk of reproductive failure, miscarriage and abnormal phenotype. Casereport: A 14 days old neonate was found to have a 46, X, der(Y)t(Y;18)(q12;q11)pat karyotype causing multiple dysmorphisms and death within one month. The proband inherited from his father(carrier) an abnormal Y chromosome with Yq deletion of regions (q12-qter) and an 18q duplication of regions (q11-qter), resulting in a severe clinical phenotype similar to Edwards syndrome (Trisomy 18 syndrome). Conclusion: These findings expand our current knowledge of the mutation spectrum of Y-autosomal translocations associated with dysmorphosis.